2016
DOI: 10.11604/pamj.supp.2016.25.1.6170
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus genotypes among chronic hepatitis B patients reporting at Korle-Bu teaching hospital, Accra, Ghana

Abstract: IntroductionKnowledge of hepatitis B virus (HBV) genotype is an important predictive variable which might have an impact in management and treatment of patients with chronic hepatitis B infection. In Ghana very little information is available on hepatitis B genotypes. This study was conducted to determine the distribution of HBV genotypes circulating among chronic hepatitis B patients reporting at the Korle-Bu Teaching Hospital (KBTH), Accra, Ghana.MethodsBlood samples (10 ml) were collected from 250 consentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…This has been attributed to mutations in the B-cell and T-cell epitopes in the S-gene of the HBV genome that may lead to breakthrough infections even among the vaccinated [ 55 ] as well as differences in the infecting genotype [ 56 ]. We did not observe a significant association between genotype A and age in conformity with the findings from other studies [ 57 , 58 ]. However, Muriel et al [ 56 ] observed a significantly increased risk of infection with genotype A among the persons aged between 29 and 41 years.…”
Section: Discussionsupporting
confidence: 92%
“…This has been attributed to mutations in the B-cell and T-cell epitopes in the S-gene of the HBV genome that may lead to breakthrough infections even among the vaccinated [ 55 ] as well as differences in the infecting genotype [ 56 ]. We did not observe a significant association between genotype A and age in conformity with the findings from other studies [ 57 , 58 ]. However, Muriel et al [ 56 ] observed a significantly increased risk of infection with genotype A among the persons aged between 29 and 41 years.…”
Section: Discussionsupporting
confidence: 92%
“…Characterization of HBV genotypes allows clinicians to determine patients’ response to treatment and potential risks of complications[ 58 , 73 ]. Flink et al[ 74 ] have indeed reported that genotype A responds better to interferon alpha and pegIFNα than genotype D. Genotype recombination occurs in areas where multiple genotypes are in co-circulation, thus facilitating diversification between individuals within the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis may be caused by viruses or by medicines or alcohol. Hepatitis has the following forms: Hepatitis A, B, C, D and E [28]: Hepatitis B: A virus commonly spread by sexual intercourse or blood transfusion or from mother to newborn at birth. Another way it spreads is by using a needle that was used by an infected person.…”
Section: Definition Of Hepatitismentioning
confidence: 99%